FINANCIAL PERFORMANCE ANALYSIS (CASE STUDY ON RIMBA BERINGIN AUTONOMOUS BUSINESS UNIT COOPERATIVE TAPUNG HULU SUB-DISTRICT YEAR 2016-2019) - Anik Sugiarti; Auzar Ali; Sri Mulyani (Jurnal Riset Manajemen Indonesia, 2020)
This research was conducted to find out the financial performance achieved by the Rimba Beringin Autonomous Business Unit Cooperative in 2016-2019 and the strategies used to achieve financial performance that meets the standards of the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No.06/Per/M.KUKM/V/2006. This research is a descriptive study. The method of data collection used is research and observation files. The data analysis method used is the financial ratio consisting of liquidity ratio and profitablity ratio. The results showed that, the financial performance of the Rimba Berin Autonomous Business Unit Cooperative as measured by the liquidity ratio of current ratio and cash ratio showed poor performance. Judging from the profitability ratio, returnt on assets and return on equity shows excellent financial performance